UNLOCKING SYNERGIES: A FRAMEWORK FOR INTEGRATING ARTIFICIAL INTELLIGENCE AND BLOCKCHAIN TECHNOLOGIES (International Journal of Intelligent Data and Machine Learning, 2025)
The confluence of Artificial Intelligence (AI) and Blockchain technologies represents a transformative frontier, promising unprecedented advancements across diverse sectors. While AI offers unparalleled capabilities in data analysis, prediction, and automation, its reliance on centralized data often raises concerns regarding integrity, privacy, and trust. Conversely, Blockchain provides decentralized, immutable, and transparent record-keeping, addressing critical trust and security issues. This article proposes a conceptual framework for understanding and leveraging the synergistic integration of AI and Blockchain. Drawing from an extensive review of contemporary literature, it delineates the mutual benefits, identifying how Blockchain can enhance AI's data integrity and security, and how AI can optimize Blockchain's efficiency and scalability. Furthermore, the article explores key applications and confronts the inherent challenges, including regulatory hurdles, technical complexities, and scalability limitations. The discussion emphasizes the profound implications of this convergence for future decentralized intelligent systems and outlines critical directions for future research and development.